Pneumococcal conjugate serotype distribution and predominating role of serotype 3 in German adults with community-acquired pneumonia. Issue 5 (29th January 2020) - Forstner, Christina; Kolditz, Martin; Kesselmeier, Miriam; Ewig, Santiago; Rohde, Gernot; Barten-Neiner, Grit; Rupp, Jan; Witzenrath, Martin; Welte, Tobias; Pletz, Mathias W.; ,
Highlights: PCV13 serotypes were present in 7.4% of German adults with pneumonia. Serotype 3 was the most common serotype detected by SSUAD. Serotype 3 can cause severe pneumonia. Serotype 3 was frequently missed by conventional microbiology. Changes in overall PCV coverage were not detected during years 2013 to 2016 in Germany. Abstract: Introduction: Implementation of the 7-valent pneumococcal conjugate vaccine (PCV7) in infant vaccination programs has substantially reduced the burden of PCV7 serotypes also in adult community-acquired pneumonia (CAP). Currently, it is unclear, if this extensive herd protection effect can be extrapolated to the additional 6 serotypes included in the 13-valent pneumococcal conjugate vaccine (PCV13), which replaced PCV7 in Germany in 2010. Objectives: We investigated changing trends for PCV13 serotypes in adult CAP patients between three to seven years after implementation of PCV13 infant immunization in Germany. Methods: Between December 2012 and January 2017, urine samples from German adult patients with radiologically confirmed CAP were prospectively collected by the multi-center cohort study CAPNETZ and analyzed by the serotype-specific multiplex urinary antigen detection assay (SSUAD) allowing for the detection of PCV13 serotypes. Results: PCV13 serotypes were found in 59 of 796 (7.4%) patients with all-cause CAP, most prevalent was serotype 3 (30 of 59 patients, 50.8%). All patients with serotype 3-CAP were admitted to hospital and the majority required oxygen at admission (83.3% of patients with serotype 3-CAP versus 50.9% of patients with pneumococcal CAP by other serotypes, p = 0.005). Compared to SSUAD testing, conventional microbiological workup missed 27 of 30 (90.0%) serotype 3-CAP cases. We could not observe a time trend in the proportions of PCV13 serotypes and serotype 3 in all-cause CAP between 2013 and 2016 (OR trend per year 0.84, 95% CI 0.64–1.11 for PCV13 serotypes and OR trend per year 0.95, 95% CI 0.70–1.28 for serotype 3). Conclusions: Conventional methods underestimate serotype 3-CAP that can cause severe disease. Changes in overall PCV13 coverage were not detected during the years 2013 to 2016, mostly driven by a high proportion of serotype 3.